2021
DOI: 10.1038/s41598-021-92893-7
|View full text |Cite
|
Sign up to set email alerts
|

SpO2/FiO2 as a predictor of high flow nasal cannula outcomes in children with acute hypoxemic respiratory failure

Abstract: The high-flow nasal cannula (HFNC) is a useful treatment modality for acute hypoxemic respiratory failure (AHRF) in children. We compared the ability of the oxygen saturation to fraction of inspired oxygen ratio (S/F) and arterial oxygen partial pressure to fraction of inspired oxygen ratio (P/F) to predict HFNC outcomes in children with AHRF. This study included children treated with HFNC due to AHRF from April 2013 to March 2019 at the Severance Children’s Hospital. HFNC failure was defined as the need for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The results were consistent with those of a previous study on hypoxic respiratory distress, which presented S/F or ROX as predictive markers for HFNC failure 8,9,11,19–21 . When the AUC of S/F was compared with ROX or ROX‐modified indices in this study, S/F was a better indicator or had a similar diagnostic value, although the index was a simpler form.…”
Section: Discussionsupporting
confidence: 91%
“…The results were consistent with those of a previous study on hypoxic respiratory distress, which presented S/F or ROX as predictive markers for HFNC failure 8,9,11,19–21 . When the AUC of S/F was compared with ROX or ROX‐modified indices in this study, S/F was a better indicator or had a similar diagnostic value, although the index was a simpler form.…”
Section: Discussionsupporting
confidence: 91%
“…The SpO 2 /FiO 2 (SF) ratio, which correlates with the partial pressure of oxygen PaO 2 /FiO 2 (PF) ratio [ 7 ], can also be utilized as a prognostic marker for acute hypoxemic respiratory failure [ 8 ]. Notably, the SF ratio has been reported as a reliable factor for predicting failure of HFNC [ 9 ] or non-invasive ventilation [ 10 ] in clinical practice when arterial blood gas sampling is not readily available. Moreover, unlike traditional respiratory failure, COVID-19 often presents with silent hypoxia, a condition where the patient has no abnormal respiratory pattern despite severe hypoxia [ 11 ]; therefore, respiratory rate may not be crucial in predicting HFNC failure in COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…However, they could not identify the accuracy of the SF ratio nor its cutoff value for outcome prediction. Kim et al [ 14 ] found that SF ratio<230 at initiation of HFNC had an AUC of 0.75 in terms of prediction of HFNC failure, which is better than that of the PF ratio. The univariate analysis revealed that SF ratio<200 at 2 hours was associated with HFNC failure in acute hypoxic respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…pROX is also easily calculated and can be used as bedside parameter. In a similar study, Yildizdas et al (16) calculated the ROX index in pediatric patients by using the respiratory Z score instead of the RR. They found that an ROX index above 66.7 at 24 hours after HFNC had 86%…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%